High-arched runners exhibit increased leg stiffness compared to low-arched runners - Williams, Dorsey S; Davis, Irene McClay; Scholz, John P; Hamill, Joseph; Buchanan, Thomas S (Gait & posture, 2004)
Leg stiffness between high-arched (HA) and low-arched (LA) runners was compared. It was hypothesized that high-arched runners would exhibit increased leg stiffness, increased sagittal plane support moment, greater vertical loading rates, decreased knee flexion excursion and increased activation of the knee extensor musculature. Twenty high-arched and 20 low-arched subjects were included in this study. Leg stiffness, knee stiffness, vertical loading rate and lower extremity support moment were compared between groups. Electromyographic data were collected in an attempt to explain differences in leg stiffness between groups. High-arched subjects were found to have increased leg stiffness and vertical loading rate compared to low-arched runners. Support moment at the impact peak of the vertical ground reaction force was related to leg stiffness across all subjects. High-arched subjects demonstrated decreased knee flexion excursion during stance. Finally, high-arched subjects exhibited a significantly earlier onset of the vastus lateralis (VL) than the low-arched runners. Differences exist in leg stiffness and vertical loading rate between runners with different foot types. Differences in lower extremity kinetics in individuals with different foot types may have implications for new treatment strategies or preventative measures.